Bannockburn : Scotland's Greatest Battle for Independence - Konstam, Angus (London Aurum Press, 2014)
This book, published to celebrate the 700th anniversary of the battle, will draw on the latest scholarship and archaeological evidence to provide a fast-paced, highly readable and clear narrative of this important story.
Include Index and Illustration
Keywords: Scotland -- Bannockburn, Battle of (Scotland : 1314)